2017
DOI: 10.1159/000479375
|View full text |Cite
|
Sign up to set email alerts
|

Two Ethnic Clusters with Huntington Disease in Israel: The Case of Mountain Jews and Karaites

Abstract: Background: Worldwide prevalence estimates of Huntington disease (HD) vary widely, with no reliable information regarding the Jewish population in Israel. Methods: This specialized tertiary single-center cross-sectional study assessed clinical, cognitive, and demographic characteristics of 84 HD patients who were treated at the Movement Disorder Unit of the Tel Aviv Medical Center, Israel. Results: Our cohort was composed of one-third Ashkenazi Jews, 27% Mountain Jews (Caucasus Jews), 18% Sephardi Jews, and 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We identified two studies that used the MoCA to assess the prevalence of cognitive impairment in an HD population 79 , 86 . Both studies were descriptive, presenting clinical and demographic characteristics of HD patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified two studies that used the MoCA to assess the prevalence of cognitive impairment in an HD population 79 , 86 . Both studies were descriptive, presenting clinical and demographic characteristics of HD patients.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, all the diagnostic test accuracy studies 71 , 72 , 76–78 were published before 2017. In the last 4 years, 14 studies reported the use of MoCA in HD patients: one prevalence study, 86 five neuroimaging studies, 83 , 85 , 87 , 94 , 95 six cognitive studies, 84 , 88 , 89 , 91 , 93 , 96 and two studies investigating clinical aspects of HD 90 , 92 . Nonetheless, the last diagnostic test accuracy study was done in 2013 77 …”
Section: Discussionmentioning
confidence: 99%